T‐cell modulation by cyclophosphamide for tumour therapy. Issue 1 (9th March 2018) - Hughes, Ellyn; Scurr, Martin; Campbell, Emma; Jones, Emma; Godkin, Andrew; Gallimore, Awen
Summary: The power of T cells for cancer treatment has been demonstrated by the success of co‐inhibitory receptor blockade and adoptive T‐cell immunotherapies. These treatments are highly successful for certain cancers, but are often personalized, expensive and associated with harmful side effects. Other T‐cell‐modulating drugs may provide additional means of improving immune responses to tumours without these disadvantages. Conventional chemotherapeutic drugs are traditionally used to target cancers directly; however, it is clear that some also have significant immune‐modulating effects that can be harnessed to target tumours. Cyclophosphamide is one such drug; used at lower doses than in mainstream chemotherapy, it can perturb immune homeostasis, tipping the balance towards generation of anti‐tumour T‐cell responses and control of cancer growth. This review discusses its growing reputation as an immune‐modulator whose multiple effects synergize with the microbiota to tip the balance towards tumour immunity offering widespread benefits as a safe, and relatively inexpensive component of cancer immunotherapy. Abstract : Cyclophosphamide modulates many aspects of the immune system, tipping the balance towards generation of anti‐tumour T‐cell responses. Findings of pre‐clinical and clinical studies indicate that the drug, particularly in synergy with the microbiota, may serve as a cheap, safe and highly effective component of cancer immunotherapy.